Neurotoxic amyloid beta oligomeric assemblies recreated in microfluidic platform with interstitial level of slow flow - Choi, Yoon Jung (Nature Publishing Group, 2013)
Alzheimer's disease is accompanied by progressive, time-dependent changes of three moieties of amyloid beta. In vitro models therefore should provide same conditions for more physiologic studies. Here we observed changes in the number of fibrils over time and studied the correlation between amyloid beta moieties and neurotoxicity. Although the number of fibrils increased dramatically, the change in neurotoxicity with time was small, suggesting that fibrils make little contribution to neurotoxicity. To study the neurotoxicity of diffusible moieties by regulating microenvironments, we created a bio-mimetic microfluidic system generating spatial gradients of diffusible oligomeric assemblies and assessed their effects on cultured neurons. We found amyloid beta exposure produced an atrophy effect and observed neurite extension during the differentiation of neural progenitor cells increased when cells were cultured with continuous flow. The results demonstrate the potential neurotoxicity of oligomeric assemblies and establish a prospective microfluidic platform for studying the neurotoxicity of amyloid beta.